THE ORDOVICIAN OSTRACODS AND ARTICULATE BRACHIOPODS FROM THE GAVRILOV YAM WELL DRILLED IN THE MOSCOW SYNECLISE - Melnikova L.M.; Dmitrovskaya Yu.E. (My University, 1997)
The results of a comprehensive study of the Ordovician lithology, ostracods, and articulate brachiopods recovered from the Ordovician part of the sections of Gavrilov Yam Wells 1 and 5 are presented. The subdivision of the Ordovician sequence is based on the regional stratigraphic scheme of the East European platform (Resolutions ..., 1992). The identified ostracod assemblage contains more than 50 species irregularly distributed throughout the section. A diverse ostracod assemblage (about 65% of the total diversity) was recovered from the Middle Ordovician deposits, but their finds in the Lower Ordovician beds were scanty. The least diverse ostracods were found in the Upper Ordovician part of the section. An analysis of the species diversity showed numerous Middle Ordovician ostracod species to be common for both the Moscow syneclise and Baltoscandia. This feature implies a close relation between these basins. Six new ostracod species are described belonging to six genera, two of which are also new. The most typical Ordovician ostracod species of the Moscow syneclise are pictured for the first time. In the studied sections, the remains of articulate brachiopods of 17 species were recovered, with the exception of one, from the carbonate deposits of the Lower and Middle Ordovician. The Upper Ordovician deposits have almost no articulate brachiopods, apparently owing to their specific, perhaps non-marine
Keywords: Ordovician; Paleozoic::Ordovician; Палеозой::Ордовикская